Strategi pengembangan kinerja tenaga kependidikan - Mawardi Mawardi (At Turots: Jurnal Pendidikan Islam, 2023)
Professionalization of education personnel development is done based on the needs of the institution, a group of teachers, and individual teachers themselves. According Danim from the perspective of an institution intended to stimulate the development of teachers, maintain, and improve the quality of staff in solving organizational problems. Furthermore it is said also that the development of teachers based on the needs of the institution is important, but the more important thing is based on the individual needs of education personnel to undergo a process of professionalization. Because the substance of the study and learning contexts evolve and change according to the dimensions of space and time, teachers are required to always improve their competence. Profession educators have the primary task of serving the community in the world pedidikan. Correspondingly, it is apparent that the professionalization in the field of education personnel implies an increase in all the power and effort in order to achieve optimal services to be provided to the public